2015
DOI: 10.9758/cpn.2015.13.3.288
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Language Ability and Cognitive Function in Patients with Schizophrenia

Abstract: ObjectiveCognitive dysfunction is common in people with schizophrenia, and language disability is one of the most notable cognitive deficits. This study assessed the use and comprehension ability of the Korean language in patients with schizophrenia and the correlations between language ability and cognitive function.MethodsEighty-six patients with schizophrenia and a group of 29 healthy controls were recruited. We assessed both clinical symptoms and cognitive functions including Korean language ability. For c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…35) In addition, another study by the present authors showed a significant correlation between language ability and K-UPSA. 36) K-WAIS, WCST, and SCoRS were conducted as cognitive function tests in this study. Intelligence, as estimated by the K-WAIS, showed strong associations with the total and functional domain scores of K-UPSA.…”
Section: Discussionmentioning
confidence: 99%
“…35) In addition, another study by the present authors showed a significant correlation between language ability and K-UPSA. 36) K-WAIS, WCST, and SCoRS were conducted as cognitive function tests in this study. Intelligence, as estimated by the K-WAIS, showed strong associations with the total and functional domain scores of K-UPSA.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with psychosis and schizophrenia with impaired social capacities have difficulty when communicating with other people, as they find it hard to recognize all these factors and integrate them into the correct message that the speaker is trying to relay [26,27]. They can get the message wrong, or misinterpret something said to them, increasing confusion and even worsening the severity of positive symptoms due to anxiety [15,18].…”
Section: Social Cognitive Impairment In Schizophreniamentioning
confidence: 99%
“…Emotion can also be transmitted via speech by using rhythm, or prosody, and some studies have demonstrated that schizophrenic patients also have difficulty recognizing vocal emotions [23,29]. When listening to sentences read with emotional intonation and without it, schizophrenic patients could not make a correct distinction, as healthy subjects did without problem [2,27].…”
Section: Social Cognitive Impairment In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Both typical and atypical antipsychotic drugs are used to treat schizophrenia 3). Many neuroimaging, biochemical, and genetic research studies done in attempts to understand the etiology and neurobiology of schizophrenia 46). These studies include the investigation of peripheral blood, an easily accessible, and thus feasible and useful, tissue to examine; genetic markers like microRNAs; and biochemical studies, which include oxidative stress levels and antioxidant capacity assays.…”
Section: Introductionmentioning
confidence: 99%